Traumatic brachial plexus injuries and current surgical correction methods Part I. Diagnosis of Traumatic brachial plexus injury - M. L. Novikov (Нервно-мышечные болезни, 2015)
The task of this paper is to familiarize practicing neurologists, neurosurgeons, traumatologists, and orthopedists with the current principles of diagnosis and treatment of different brachial plexus injuries (BPI). The anatomy of the brachial plexus is described in detail; the main mechanisms of its injuries are considered and their current classification is given. Particular emphasis is laid on the traction-based mechanism of BPI and its basic treatment in a group of patients who require (need) surgical treatment. The capabilities of various instrumental techniques, such as X-ray, neuroimaging, electrophysiological, in the diagnosis of BPI are considered. The author’s algorithm for a differential diagnostic search is proposed in this pathology.